Portugal’s ‘Weekend at the coast’: Fort Jesus and empire celebration in Kenya - Sarmento, João Carlos Vicente (2011)
This chapter analyses how these ‘global’ celebrations collided with the British colonial experience and evolution in 1950s Kenya, and traces the convergence of two imperial trajectories at a particular colonial building in Mombasa, Kenya. On the one hand, the British were trying to order the colony, combating a truly negative image of East Africa at home, and setting up a museum at Fort Jesus Museum, a sixteenth-century Fort, seemed to be a step in the right direction. On the other hand, an intricate political development in the creation of a foundation in Portugal led to a sudden funding that made the restoration of Fort Jesus possible, allowing also for an exaltation of this colonial legacy.